(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: Achieving the main governance systems represented by transparency and disclosure requires the presence of international standards that contribute to strengthening them in accordance with current requirements. International Financial Reporting Standards (IFRS) and Integrated Reporting (IIRC) are the basic pillar in strengthening governance systems. From this standpoint, the research aims to demonstrate the integration between... International Financial Reporting Standards (IFRS) and Integrated Reporting (IIRC) to enhance governance systems and the extent to which this is reflected in sustainable performance, which constitutes the challenge faced by economic units today as it represents the value that these units can achieve. To achieve the objectives of the research, a sample of listed banks was selected. In the Iraq Stock Exchange, which are the Assyria International Bank, the United Bank for Investment and Finance, the Commercial Bank of Iraq, and the National Bank of Iraq, through a questionnaire. The number of questionnaires distributed reached (215), while the number of questionnaire respondents reached (164). For the purposes of research and analysis, ( 152) questionnaires, and (12) questionnaires were excluded due to inaccuracy in the answers. They were analyzed according to statistical methods (arithmetic mean, standard deviation, frequency distributions and percentages) by adopting the SSPS program to obtain the results, and from the results that were reached, achieving transparency and disclosure Proper adoption of integration between international financial reporting standards and integrated reports by including the financial statements of economic units on all financial and non-financial information would lead to creating a climate in which there is trust and credibility in the information and comparability in a way that serves the users of those lists, which is reflected in the creation of a competitive advantage and thus Sustainable performance of economic units.